STRATEGI GURU DALAM MENANAMKAN SIKAP TOLERANSI PADA SISWA DALAM MENANGGAPI PERBEDAAN KEYAKIAN - Ahmad Hariandi; Fazria Fazria; Fatma Cahyana; Rozi Rozi; Siti Patimah (Tadrib: Jurnal Pendidikan Agama Islam, 2020)
Tolerance is an attitude of mutual respect for diversity. In the school environment, students are faced with various differences, so that tolerance is an important attitude that must be owned by students, this is inseparable from the teacher's strategy in instilling tolerance in the classroom. a form of religious tolerance that is implementing mutual respect and respect for the beliefs held by others. This means that differences found in the surrounding environment are not used as an excuse to be hostile to others but are able to live side by side among these differences. The aim is to find out the teacher's strategy in instilling tolerance in students in responding to differences in beliefs by using a qualitative descriptive approach and this type of research is a phenomenological study. Data collection is done by observation and interview techniques to meet research needs. Then analyzed with data reduction techniques, data display and data verification. Diversity of religions that cannot contradict can create different groups. A happy attitude in supporting the diversity that is executed can help well because it has a supporting role. The strategies taken by teachers in schools that have students of different religions will succeed without visible conflicts that are motivated by diversity. The role of the teacher is very important in instilling religious borrowing attitudes both through role models and through activities held at school. The researcher hopes that this journal can add insight to the readers and the researcher suggests that the handling of students' tolerance in facing differences in belief not only come from the teacher or the school but also includes tri education centers (family, community, and school) because of tolerance This is very important for every individual to have at the earliest possible age.